THE EFFECT OF USING THE MEDIA APPLICATION TIKTOK IN LEARNING THE JAPANESE LANGUAGE LEARNING : A STUDY AT SMA NEGERI 1 TONDANO - Wuisang, Justien R. R.; Sirait, Marenita J.; Lensun, Sherly F. (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
The effect of using the media application of Tik-Tok in learning at SMA Negeri 1 Tondano. It is one of the alternative effective learning media in Japanese vocabulary. This study aims to improve student learning outcomes in Japanese subjects by teaching using the Tik-Tok application so students can understand Japanese vocabulary. The research method used in this research is the experimental method, and the research technique is data processing based on the t-test. From the results of the pretest and post-test, the result of hypothesis testing using t-test statistics, the results are obtained where count =6,4>ttabel = 1,704 so that the average students learning outcomes taught using the Tik-Tok application media were better than the average students learning outcomes taught without using the Tik-Tok application.